Penyuluhan Untuk Meningkatkan Kewaspadaan Risiko Penyakit Tuberkulosis Pada Penderita Diabetes Mellitus - Saputra, Firman Firdauz; Kusumawardani, Eva Flourentina; Paradhiba, Meutia; Rimonda, Rubi; Siahaan, Perry Boy Chandra; Putra, Onetusfifsi; Fadillah, Mardi (Idea Pengabdian Masyarakat, 2022)
Tuberculosis (TB) is still one of the infectious diseases that burden the community, and this condition is exacerbated by the increase in degenerative diseases such as Diabetes Mellitus (DM). Diabetes Mellitus as the 'mother of disease' makes people more susceptible to infectious diseases, which as TB. In addition, DM also reduces the cure rate for TB disease suffered by the community. With these conditions, the team decided to conduct health education for the people of Gebang Village to increase knowledge and public awareness of the risk of TB disease in DM patients. The counseling was conducted at the Gebang CFG Health Center. Counseling was carried out using the Lecture method and the media leaflet, discussion, and question and answer. Evaluation of the implementation of counseling was carried out by looking at the number of participants' attendance and the increase in community knowledge. The results of the evaluation carried out stated that the attendance of participants was 100%. The results of the evaluation of increasing knowledge from the results of the pre-test and post-test, where the results of the analysis showed a significant difference in knowledge between the pre-test and post-test of the participants. Increased knowledge in the community was expected to increase public awareness of the risk of TB disease in DM to create an independent community to maintain their health.